Component Analysis and Determination of Heavy Metal Accumulation in Euphorbia macroclada Boiss (Nigde, Turkey) - Battaloglu, Rifat; Candar, Sabri; Gurhan Yalcin, M.; Yalcin, Fusun (Asian Journal of Chemistry, 2013)
This study reports the heavy metal concentration of the plant macroclada boiss belonging to the Euphorbia type. Twenty stations which have different distances and different heights to the highway were chosen for this study from the separation of Nigde-Adana D750 highway Ali Hoca and Maden Village to Maden Village (Nigde, Turkey). The Cd, Cr, Cu, Ni and Pb concentrations of the sediment and plant samples got from those stations were studied through the ICP-OES technique. According to the arithmetic mean of the chemical analyses results, the highest values are Cr, Pb, Cu, Ni and Cd in earth; Ni, Cr, Cu, Pb and Cd in plants. The maximum values were shown in Cd: S1; Cr: S3; Cu: S10; Ni: S1; Pb: S3 stations in the earth and in Cd:S1; Cr: S1; Cu: S1; Ni: S1; Pb: S1stations in the plants. A high relationship level was defined between Cd vs. Cr, Ni, Pb; Cr vs. Ni, Pb and Ni vs. Pb in the earth and between Cd vs. Cr, Cu, Pb; Cr vs. Cu, Ni, Pb; Cu vs. Pb and Ni vs. Pb in the plants. According to the component analysis, the first factor is Cd, Cr, Ni, Pb and the second factor is Cu. On the other hand, the only factor represented the whole in the plants. The Model Summary analysis results in the earth is R2 = 0,909 %, in the plant R2 = 0,907 % and the samples were explained on a relatively high level. It was thought that the origins of the heavy metals showing positive high level relation are the same and the analysis area of Nigde-Adana D750 intercity highway are affected negatively due to the traffic.